2020
DOI: 10.3390/app10010383
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Fruit Identification Algorithm in Orchard Conditions to Develop Robots Using Video Processing and Majority Voting Based on Hybrid Artificial Neural Network

Abstract: The first step in identifying fruits on trees is to develop garden robots for different purposes such as fruit harvesting and spatial specific spraying. Due to the natural conditions of the fruit orchards and the unevenness of the various objects throughout it, usage of the controlled conditions is very difficult. As a result, these operations should be performed in natural conditions, both in light and in the background. Due to the dependency of other garden robot operations on the fruit identification stage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…We used well-known performance indices: mean square error (MSE), root-mean-square error (RMSE) and mean absolute error (MAE). We also computed common regression (R) and determination (R 2 ) coefficients ( Pourdarbani et al., 2020 ; Sabzi et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…We used well-known performance indices: mean square error (MSE), root-mean-square error (RMSE) and mean absolute error (MAE). We also computed common regression (R) and determination (R 2 ) coefficients ( Pourdarbani et al., 2020 ; Sabzi et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most methods published on a non-destructive estimation of fruit properties are based on samples collected and assessed under controlled laboratory conditions after fruit temperature equilibration [37]. Predictions of non-destructive methods based only on internal validations tend to be overestimated in the literature.…”
Section: Comparison Of the Proposed Methods With Other Researchersmentioning
confidence: 99%
“…According to previous research, it is found that many studies have been accomplished on potatoes, most of them focused on the detection of visible defects and normally using a single detection algorithm. The innovation of the present study is the proposal, development, and validation of an ensemble classifier, combined with the majority voting rule [ 23 ] that includes hybrid artificial neural networks (ANN) and imperialist competitive algorithm (ANN-ICA), hybrid ANN and harmony search algorithm (ANN-HS), linear discriminant analysis (LDA), and k-nearest neighbors algorithm (KNN), to identify internal defects of potatoes that have no visible symptoms.…”
Section: Introductionmentioning
confidence: 99%